2023
DOI: 10.1039/d3ce00736g
|View full text |Cite
|
Sign up to set email alerts
|

Hexnuclear, octanuclear, dodecanuclear, and hexadecnuclear polyoxomolybdenum(v)-based porous materials for selective adsorption of gases

Rong-Yan Lin,
Ru-Dan Dai,
Xin Dong
et al.

Abstract: Neutral hexnuclear and octanuclear polymolybdate-based porous complexes [Mo6O6(μ2-O)9(Hbtz)6]·21H2O (1, Hbtz = 1H-benzotriazole) and [Mo8O8(μ2-O)12(Hdatrz)8]·28H2O (2, Hdatrz = 1H-1,2,4-triazole-3,5-diamine), dodecanuclear and hexadecnuclear complexes Na4[Mo12O12(μ2-O)4(μ3-O)12(3-trz)8]·14H2O (3, 3-trz = 1,2,4-triazol-3-amine) and Na8[Mo16O16(μ2-O)16(μ2-OH)16(3-trz)8]·29H2O (4)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…5. In previous studies, octanuclear molybdenum porous structures have been reported with molecular formulas of [Mo 8 O 8 (μ 2 -O) 12 (Hdatrz) 8 ]·28H 2 O (Hdatrz = 3,5-diamino-1 H -1,2,4-triazole), 25 Na 8 [Mo 16 O 16 (μ 2 -O) 16 (μ 2 -OH) 16 (3-trz) 8 ]·29H 2 O (3-trz = 3-amino-1 H -1,2,4-triazole), 25 [Mo V 8 O 8 (μ 2 -O) 12 (Htrz) 8 ]·62H 2 O (Htrz = 1 H -1,2,3-triazole) 26 and [Mo V 8 O 8 (μ 2 -O) 12 (Htrz) 8 ]·30H 2 O. 27 The inner diameters formed by these complexes are 4.0 Å, 4.7 Å, 4.8 Å and 5.1 Å, and the pore sizes formed between the molecules are 6.0 Å, 9.0 Å × 4.4 Å, 7.1 Å × 4.8 Å and 12.2 Å × 6.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5. In previous studies, octanuclear molybdenum porous structures have been reported with molecular formulas of [Mo 8 O 8 (μ 2 -O) 12 (Hdatrz) 8 ]·28H 2 O (Hdatrz = 3,5-diamino-1 H -1,2,4-triazole), 25 Na 8 [Mo 16 O 16 (μ 2 -O) 16 (μ 2 -OH) 16 (3-trz) 8 ]·29H 2 O (3-trz = 3-amino-1 H -1,2,4-triazole), 25 [Mo V 8 O 8 (μ 2 -O) 12 (Htrz) 8 ]·62H 2 O (Htrz = 1 H -1,2,3-triazole) 26 and [Mo V 8 O 8 (μ 2 -O) 12 (Htrz) 8 ]·30H 2 O. 27 The inner diameters formed by these complexes are 4.0 Å, 4.7 Å, 4.8 Å and 5.1 Å, and the pore sizes formed between the molecules are 6.0 Å, 9.0 Å × 4.4 Å, 7.1 Å × 4.8 Å and 12.2 Å × 6.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%